How does innovative customer knowledge influence electronic word-of-mouth recommendation behavior through egoistic and altruistic approaches? Testing a moderated mediation model - Qi, Xiaobo (Frontiers in Communication, 2024)
IntroductionAt present, innovative customer knowledge on social media platforms is mostly treated as a kind of “self-entertainment” activity content, and has not been effectively integrated and used by sales-oriented social media enterprises. As a result, the problem of electronic word-of-mouth recommendation reducing for such enterprises is more prominent. Theoretically, on the one hand, researches in the field of customer knowledge are mainly concentrated in the field of knowledge management led by the enterprise, which lacks to discuss the influence of innovative knowledge on electronic word-of-mouth recommendation behavior from the perspective of customer dominance. On the other hand, previous studies lack to explore the formation mechanism of electronic word-of-mouth recommendation behavior of innovative customers from the dual paths of altruism and egoism. The professional characteristics and social characteristics of innovative customers are not analyzed as boundary conditions. In this context, based on social learning theory and social identity theory, this study explores the influence mechanism of innovative customer knowledge on electronic word-of-mouth recommendation behavior.MethodsData were collected by Likert 5-level scale using questionnaire survey method. A total of 452 valid questionnaires were collected from Northeast, Northwest, East, North, Central, South and southwest China by random sampling method. SPSS21.0 software and Bootstrap (PROCESS3.0) program were used to analyze the multilevel linear regression, structural equation model and robustness test of the model.Results(1) Innovative customer knowledge had a significant positive impact on electronic word-of-mouth recommendation behavior and professional identity; (2) Professional identity had a significant positive effect on electronic word-of-mouth recommendation behavior; (3) Professional identity played mediating role between innovative customer knowledge and electronic word-of-mouth recommendation behavior; (4) Compared with high professional status and high social status, low professional status and low social status had a stronger moderating effect on the relationship between professional identity and electronic word-of-mouth recommendation behavior, and there was a moderated mediation effect.DiscussionInnovative customer knowledge generates electronic word-of-mouth recommendation behavior through two paths: altruism and egoism. These two paths are affected by the external characteristics of innovative customers, that is, professional characteristics and social characteristics have a moderating effect on them.